Solvent Evaporation Method and Crystal Structure of [5-Benzoyl-2-methyl-4-(1-phenyl[1,2,3]triazolidin-4-ylmethoxy)benzofuran-7-yl]phenyl-methanone - Zhang, L.; He, Y.X. (Asian Journal of Chemistry, 2014)
One new compound i.e., [5-benzoyl-2-methyl-4-(1-phenyl[1,2,3]triazolidin-4-ylmethoxy)benzofuran-7-yl]phenyl-methanone with m.f. C32H23N3O4 has been successfully synthesized by 1-azidobenzene, the appropriate alkyne, copper sulphate and sodium ascorbate. Compound shows a one-dimensional framework. The 3D supramolecular structure is formed via hydrogen bonding connection.